Another version of “exotic characterization of a commutative H∗-algebra” - Parfeny P. Saworotnow (International Journal of Mathematics and Mathematical Sciences)
Commutative H∗-algebra is characterized in a somewhat unusual fashion without assuming either Hilbert space structure or commutativity. Existence of an involution is not postulated also.